Immunity to Environmental Crime, Harm and Violence: An Ongoing Pandemic and a Possible Narrative Vaccine - Brisman, Avi (International journal of offender therapy and comparative criminology, 2022)
As of June 2020, there have been at least 2,540 mass shootings since the Sandy Hook Elementary School shooting in Newtown, CT, on December 14, 2012. Some have suggested that the repeated trauma of these massacres has created a collective ?emotional numbness,? lessening our empathy. This article asks whether a similar phenomenon is occurring with respect to environmental crime and harm. It considers whether we have developed ?compassion fatigue? regarding environmental violence and contemplates a ?workout regimen? for empathy for Gaia?s suffering. In so doing, it seeks to engage with emerging work in the penumbra of narrative criminology and green cultural criminology.